2008
DOI: 10.1159/000142099
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Mesangial Cell Alpha-Smooth Muscle Actin Expression in 3-Dimensional Matrix by High Glucose and Growth Factors

Abstract: Background/Aims: We postulated that α-smooth muscle actin expressed in primary cultured mesangial cells is down-regulated in 3-dimensional (D) culture and up-regulated by high glucose and growth factors. Methods: Primary rat mesangial cells were growth-arrested in 5.6 mM (NG) or 30 mM (HG) glucose for 14 days in 3-D Matrigel. Alpha-SM actin expression was analyzed by immunoblotting, real-time PCR and by α-SM actin promoter activity in response to 24 h stimulation with endothelin-1 (ET-1), angiotensin II (Ang I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 70 publications
1
5
0
Order By: Relevance
“…The increased Ca 2+ is in turn needed by other proteins found in the reticuloplasm like GRP78 or PDIA3 [ 29 ]. These observations of regulated changes in actin cytoskeletal protein and calcium binding protein expression, when taken together, are consistent with the known responses of mesangial cells to HG under more chronic conditions [ 30 , 31 ].…”
Section: Discussionsupporting
confidence: 87%
“…The increased Ca 2+ is in turn needed by other proteins found in the reticuloplasm like GRP78 or PDIA3 [ 29 ]. These observations of regulated changes in actin cytoskeletal protein and calcium binding protein expression, when taken together, are consistent with the known responses of mesangial cells to HG under more chronic conditions [ 30 , 31 ].…”
Section: Discussionsupporting
confidence: 87%
“…Accumulating evidence suggests that increased pericyte proliferation has a fundamental role in the pathological processes of fibrosis, inflammation, thrombosis and vessel calcification . Studies have shown that pericytes transdifferentiate into myofibroblasts under profibrotic stimulations . Recent studies have also demonstrated endothelial HIF hydroxylase system plays a critical role in vascular remodelling .…”
Section: Discussionmentioning
confidence: 99%
“…The effects of an ARB on glomerular sclerosis may be dependent on complex interactions between several factors that mediate mesangial matrix expansion. Several cell culture studies have indicated that high glucose-induced mesangial cellular injury cannot be completely blocked by ARBs [35,36]. Fioretto et al .…”
Section: Discussionmentioning
confidence: 99%